PENGARUH PROFITABILITAS, KOMISARIS INDEPENDEN, DAN INTENSITAS ASET TETAP TERHADAP MANAJEMEN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Prastyatini, Sri Lestari Yuli; Efriyendi, Novit (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Tax management can be influenced by various factors. This research was conducted to test whether profitability, independent commissioners, and fixed asset intensity have an effect on tax management. This research is quantitative in nature where the results of the research data are in the form of numbers. The data used in this research is annual financial report data from manufacturing companies listed on the Indonesia Stock Exchange (BEI) for 2017-2021. Data collection was carried out using a non-participant observer method, where the author only observed the data available on the website www.idx.co.id. The number of manufacturing companies used as samples for this research was 15 manufacturing companies with a total of 75 annual financial report data that had been searched. The data analysis used was multiple linear regression and hypothesis testing using SPSS 25. The results showed that profitability had no effect on tax management, while independent commissioners and fixed asset intensity had a positive effect on tax management.